2020
DOI: 10.17582/journal.pjz/20191203161254
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Altered Pattern of Antibiogram and Biofilm Character in Staphylococcus aureus Isolated From Dairy Milk

Abstract: Photoperiod and shelter have direct or indirect effects on phenotypic traits expression in different fish species. The present study was, therefore, intended to explore whether these light and shelter could influence some phenotypic traits of African catfish larvae under laboratory condition. Newly hatched larvae were stocked in plastic aquaria (10L) at a rate of 5 individuals/L and reared for one month under four treatments such as 24h light (24L), 24 h dark (24D), 12h light and 12h dark with PVC (12DL_PVC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Staphylococcus aureus is a major causative agent of intramammary infections in dairy animals with potential virulence of surface components (adhesins, capsular polysaccharides, protein A), toxins, extracellular enzymes and coagulase [21]. About 74% quarter prevalence of S. aureus in bovine udder [22] with overall prevalence exceeding 61% in dairy animals [4]. A wide array of genotypic variations has been observed with great genetic diversity in the isolates of bovine as well as caprine origin.…”
Section: Staphylococcus Aureus Strains Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…Staphylococcus aureus is a major causative agent of intramammary infections in dairy animals with potential virulence of surface components (adhesins, capsular polysaccharides, protein A), toxins, extracellular enzymes and coagulase [21]. About 74% quarter prevalence of S. aureus in bovine udder [22] with overall prevalence exceeding 61% in dairy animals [4]. A wide array of genotypic variations has been observed with great genetic diversity in the isolates of bovine as well as caprine origin.…”
Section: Staphylococcus Aureus Strains Spectrummentioning
confidence: 99%
“…Therefore, to take an accurate decision to control the mastitis depends on understanding of economic impact of mastitis [43,53]. Mastitis is among the main reason in cattle for the use of antibiotics and this exposure of animal to antibiotics is main reason behind the development of antibiotic resistant bacteria and antimicrobial residues in milk which are of a great public health concern [4,7].…”
Section: Veterinary and Medicinal Costmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the disease is also very important from the consumer's health risk point of view [6]. The presence of heat-resistant pathogenic spores and toxins in commercially available raw milk poses a serious threat to consumer's health and wellbeing [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the implementation of mastitis control strategies such as 5-point mastitis control program and later on 10-point mastitis control program by National Mastitis council, contagious mastitis pathogens were considered as the main causative agents of mastitis in dairy cows, even in developed countries [14][15][16]. The epidemiological field study of mastitis concluded that agents such as Staphylococcus aureus, Streptococcus agalactiae and Escherichia coli account for over 75% of mastitis cases, and Staphylococcus aureus is the most prevalent, resistant and challenging candidate among them [8,15,17]. The bacterial entry into mammary glands leads to bacteria interaction with the mammary epithelial cells, resulting in local inflammatory signs and deteriorated milk quality.…”
Section: Introductionmentioning
confidence: 99%